(N|KOSISTEMY WOSTO^NYH POGRANI^NYH TE^ENIJ I CENTRALXNYH RAJONOW tIHOGO OKEANA (B/s - (NwINOGRADOW(B, (NmIHAIL eWGENXEWI^s; (NmUSAEWA(B, (N|(B.(Ni(B.s; (NiNSTITUT OKEANOLOGII IM(B. (Np(B.(Np(B. (N{IR[OWA an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 281-282s
Keywords: (N|KOLOGI^ESKIE SISTEMY MORSKIE (B- (NtIHIJ OKEANs